Strategi Pengembangan Pariwisata Pedesaan: Integrasi Analisis Spasial dan SWOT di Kecamatan Songgon, Banyuwangi - Tri Rafika Diyah Indartin; Muhammad Asyroful Mujib; Eva Kurniasari; Hablana Rizka; Firda Diartika (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
The development of sustainable tourism in rural highland areas requires a spatially integrated and community-based management approach. This study aims to formulate strategic directions for tourism development in Songgon District, Banyuwangi Regency by integrating spatial analysis and SWOT evaluation. Spatial analysis was conducted using the Nearest Neighbor Analysis (NNA) method to assess the distribution pattern of ten natural tourism destinations across four villages. The results of the NNA analysis show a value of 1.18 (NNA>1), indicating that the distribution pattern of tourist sites is somewhat dispersed (not clustered) and not extremely scattered. These findings suggest the presence of spatial decentralization of tourism assets, which requires connectivity and thematic integration between locations. SWOT analysis, supported by field interviews, identified internal and external factors classified into four strategic typologies: Strength-Opportunity (S-O), Strength-Threat (S-T), Weakness-Opportunity (W-O), and Weakness-Threat (W-T). The S-O strategy emphasized strengthening existing attractions and community-based ecotourism; S-T focused on enhancing local identity to withstand environmental and market pressures; W-O highlighted infrastructure improvement and digital transformation; while W-T addressed fundamental service gaps and external threats simultaneously. The integration of NNA and SWOT provided a comprehensive foundation for contextual, adaptive, and data-driven tourism planning in Songgon District. This approach offers transferable insights for tourism development in other rural regions with similar socio-ecological complexities.